Transapical mitral valve-in-ring procedure with a novel self-expandable transcatheter heart valve: first- and last-in-man report. (20th December 2019) - Schaefer, Andreas; Seiffert, Moritz; Blankenberg, Stefan; Conradi, Lenard
Abstract: Interventional therapy of failing surgical mitral valve replacement and repair is an appealing option in patients who are not eligible for redo surgery. We herein report on the first-in-human use of a repositionable, self-expandable transcatheter heart valve with motorized delivery for a transapical mitral valve-in-ring procedure. After implantation, fluoroscopy showed no residual regurgitation and pressure measurements did not reveal any signs of left ventricular outflow tract obstruction.